2007
DOI: 10.1007/s12038-007-0115-z
|View full text |Cite|
|
Sign up to set email alerts
|

Age-dependent increase in green autofluorescence of blood erythrocytes

Abstract: Green auto-fluorescence (GAF) of different age groups of mouse blood erythrocytes was determined by using a double in vivo biotinylation (DIB) technique that enables delineation of circulating erythrocytes of different age groups. A significant increase in GAF was seen for erythrocytes of old age group (age in circulation more than 40 days) as compared to young erythrocytes (age less than 15 days). Erythrocytes are removed from blood circulation by macrophages in the reticulo-endothelial system and depletion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…This autofluorescence is associated with aging and has been attributed to the accumulation of Hb degradation products. 42,43 Quantification of AF 520 RBCs by flow cytometry ( Figure 6F) showed that they were enriched in SHIVA but also PA low mice, showing that this phenotype is dissociated from the SHIVA genetic background and associated with mice with PA low . Because Sox17 has been shown to regulate fetal hematopoiesis, we tested whether this AF 520 phenotype might be cell autonomous.…”
Section: Pantetheinase Modulates Severe Malariamentioning
confidence: 99%
“…This autofluorescence is associated with aging and has been attributed to the accumulation of Hb degradation products. 42,43 Quantification of AF 520 RBCs by flow cytometry ( Figure 6F) showed that they were enriched in SHIVA but also PA low mice, showing that this phenotype is dissociated from the SHIVA genetic background and associated with mice with PA low . Because Sox17 has been shown to regulate fetal hematopoiesis, we tested whether this AF 520 phenotype might be cell autonomous.…”
Section: Pantetheinase Modulates Severe Malariamentioning
confidence: 99%
“…In an earlier report, enhanced PS externalization was demonstrated on aged populations of erythrocytes using FITC-tagged annexin [4]. Although we could reproduce these results, we found that if phycoerythrin (PE)-tagged annexin was used to detect PS, no change in PS expression was found on aged erythrocytes [19].…”
Section: Aging Of Erythrocytes and Susceptibility To Carbon Nanotubesmentioning
confidence: 45%
“…Similarly, old erythrocytes are not significantly enriched in heaviest fractions (young/old ratios 0.48 and 0.65, Mouse erythrocytes were biotinylated as per Protocol B and fractionated on a Discontinuous PDG with five layers of densities .,0650 ± 0.004, 1.0711± 0.006, 1.0782 ± 0.008, 1.0858 ± 0.004 and 1.0883 ± 0.003 g/ml prepared as described before [19]. Erythrocytes in different buoyant density fractions were stained with streptavidin-APC followed by flow cytometric analysis.…”
Section: Random Elimination Of Erythrocytes Versus Elimination Of Agementioning
confidence: 99%
“…A phenomenon like that can also play a role in long-stored units of non-leukoreduced RBCs presented now. During storage, residual leucocytes release cytokines, enzymes and other bioreactive molecules which can alter the RBC membrane and increase RBC adherence to endothelial cells [21,22].…”
Section: Discussionmentioning
confidence: 99%